Information modelling with focus on existing manufacturing systems. (2021) - Schmied, Sebastian; Mathias, Selvine G.; Großmann, Daniel; Müller, Ralph Klaus; Jumar, Ulrich
Abstract: Manufacturing systems are frequently required to adapt to changes. To support these, a standardized, semantic exchange of information between all components of the system is crucial. An information model describing all information available within the manufacturing system together with a common middleware protocol is able to fulfil this requirement. To create an information model, it is relevant to identify information objects and their relations to each other. The implementation of a common address space requires further concepts like dynamic aggregation of entities. Therefore, this article describes a methodology for information model creation including versioning compliant modelling and integration of existing standards. Further, steps for implementation as validation and dynamic aggregation of instances are described. The results of this approach have been discussed in the following sections along with the proposal for further directions and an application example.